Alface americana fertirrigada com diferentes doses de ácido fosfórico e hidróxido de potássio - Deus, Angélica Cristina Fernandes [UNESP]; de Oliveira Costa, Carla Deisiane [UNESP]; Foratto, Letícia Cecília [UNESP]; Fernandes, Dirceu Maximino [UNESP]; Carribeiro, Lívia Sancinetti [UNESP] (My University, 2011)
Fertirrigation with phosphoric acid has been considered as an option to avoid drips from clogging. In some cases, this acid cause soil acidification and it can be substituted bypotassium hydroxide. This study had the objective of evaluating the effects of different phosphoric acid and potassium hydroxide doses, applied via fertirrigation, on soil fertility, plant nutrition and lettuce yield, compared to the conventional fertilization system. The experiment was carried out in greenhouse, in the College of Agricultural Sciences, FCA/UNESP, Botucatu-SP-Brazil. The experimental design was the completely randomized block, with 6 treatments and 4 replications. Treatments consisted of the combinations of doses (25% and 50% of the recommended complete dose for the lettuce) and application ofcomplete dose (100%) of phosphorus (P) and potassium (K) applied via fertirrigation, and a control (conventional fertilization system). The results showed that P and K availability in soil and nutrient concentration in plants were affected by treatments. Low phosphorus and potassium doses, applied via fertirrigation, were not efficient for the appropriate development of lettuce plants. The results showed that agronomic characteristics and commercial lettuce were affected by doses and application systems, especially the treatment with application of P and K full dose fertirrigation.

A fertirrigação com ácido fosfórico tem sido uma opção para evitar o entupimento de gotejadores, porém a utilização do mesmo causa acidificação do solo, e para tal problema uma alternativa é o uso de hidróxido de potássio. O trabalho teve por objetivo verificar o efeito de diferentes doses de ácido fosfórico e hidróxido de potássio via fertirrigação comparando-o com a adubação convencional na fertilidade do solo, nutrição e produção de alface. O experimento foi conduzido em casa de vegetação, na Faculdade de Ciências Agronômicas, campus de Botucatu/UNESP. O delineamento experimental foi em blocos ao acaso com 6 tratamentos e 4 repetições. Os tratamentos constituíram-se de combinações entre doses (25% e 50% da dose completa recomendada para a alface) e aplicação de dose completa (100%) de fósforo (P) e de potássio (K), aplicadas via fertirrigação e uma testemunha com aplicação de dose completa na forma convencional. A disponibilidade de P e K no solo e a concentração destes nutrientes na planta foram influenciadas pelos tratamentos. A redução das doses de P e K aplicadas via fertirrigação mostrou-se ineficiente para o bom desenvolvimento da cultura de alface. Os tratamentos influenciaram significativamente as características agronômicas e comerciais da alface, destacando-se o tratamento com aplicação de dose completa de P e K via fertirrigação.
Crisphead lettuce fertirrigated with different phosphoric acid and potassium hydroxide doses
Keywords: Acidity; Dripping; Latuca sativa l.; Soil fertility; Wet bulb; acidity; crop yield; drip irrigation; experimental design; fertilizer application; hydroxide; leafy vegetable; nutrient availability; nutrient use efficiency; phosphorus; potassium; soil fertility; soil nutrient; Botucatu; Brazil; Sao Paulo [Brazil]; Lactuca